PENGARUH STRATEGI PEMBELAJARAN DAN KECEMASAN TERHADAP HASIL BELAJAR MATEMATIKA - Rusmono -; M. Yusro (FTK Universitas Pendidikan Ganesha, 2010)
The research is intended to discover the effect of instructional strategies and math anxiety onlearning outcomes in mathematics. Factorial design 2 x 2 was employed in order to answer theresearch question how the effect of the instructional strategies and math anxiety on learning outcomesin mathematics.The study supports the following hypotheses: 1) in general, students who were taughtby using problem based learning (PBL) strategy had higher learning outcomes than those taught byexpository strategy, 2) students with higher math anxiety who were taught by using PBL strategy hadhigher learning outcomes than those by expository strategy, 3) students with lower math anxiety whowere taught by PBL strategy had lower learning outcomes than those by expository strategy, and 4)there was an effect of interaction between instruction strategies and math anxiety on students learningoutcomes in mathematics. It means that the effect of instructional strategies has a correlation with thecharacteristic of the students who engage in teaching learning process. It implies that there is nosingle instructional strategy that gives better result on learning outcomes in mathematics for allstudents with the different math anxieties. Based on this research findings mathematics vocationalteachers in the field of technology and industry should apply several instructional strategies to servestudents with different math anxieties.Kata Kunci: Hasil Belajar Matematika, Kecemasan, Strategi PBL.